Acts : A Commentary - Pervo, Richard I. (Book collections on Project MUSE., 2008)
"The Acts of the Apostles joins the Gospel of Luke with the ministry of Paul. Renowned New Testament scholar Richard I. Pervo shows how this masterful storyteller worked his magic, drawing on first-century literary techniques of narration and characterization. Luke's literary skills did not prevent scribes from re-writing his masterwork, however, the textual tradition of Acts is among the most intriguing of the documents of the New Testament, and is a focus here." "Pervo's commentary provides a compelling interpretation of Acts in the context of Hellenistic literature and the emerging Christian movement, Readers will rediscover the "profit with delight" that was the ideal of ancient story-tellers."--Jacket